Analysis and Research on Badminton Spot Tactics Based on Computer Association Rules Mining. Issue 3 (October 2020) - Lei, Wei; Yu, Kemeng
Abstract: The ubiquitous rhythm in competitive sports activities not only affects athletes' competitive style and performance, but also determines their performance to a certain extent. The research on the basic theory and empirical application of competition rhythm will help improve the athletes' cognitive level of competition activities. The analysis and elaboration of the basic theoretical problems of badminton competition rhythm based on computer association rules mining can solve many practical problems such as the application and control of badminton competition rhythm in sports training and competition, and establish badminton competition rhythm theory. In addition, it also has important research significance and value for the practical application of badminton.